Cow hoof diseases’ diagnostics - Klymas, A.; Simitko, O. (Scientific Progress & Innovations, 2025)
The distal part of cows’ extremities is important for ensuring the animals’ movement and has a direct impact on their health and productivity. Cow hoof diseases are a serious problem for farms and owners of animals as such diseases lead to a considerable decrease in milk productivity and cows’ untimely culling; therefore, the studies as to finding the spread of support and movement organs’ pathologies under the specific conditions of cows’ keeping is an important direction of researches, which allows veterinary doctors conduct sanitary measures in time. The purpose of the conducted study was the monitoring as to cow hoof pathology on dairy-commodity farm and substantiating the expediency of using Hofmir apparatus created by the team of authors to reveal hoof pathology of cows at early stages. The work was performed on dairy-commodity farm of “Agroecology” private enterprise (the village of Pokrovske, Myrhorod district, Poltava region). The work was done during 2022–2023. As a result of analyzing the reporting veterinary documentation, it was found that orthopedic pathology among cow stock is a serious problem in the conditions of the studied farm. It was also known that the share of orthopedic cow diseases among the total number of the studied stock was 11.0 % in 2022. In 2023, the number of diseased animals increased a little and made 11.4 % of the total amount of the investigated stock. A high level of support and movement organs’ pathologies among the cows on the dairy-commodity farm enabled to conduct the approbation of Hofmir apparatus and the algorithm of conducting the diagnostics. As a result of the diagnosis, it was found that on the dairy-commodity farm, using the suggested Hofmir apparatus and the algorithm for performing, 24 cows with hoof deformations were found (the animals that had deviations from the normative values in the indicator of the fore wall angle with the bearing surface). It was determined that on the right hind leg, the average value of the toe angle on the lateral hoof was 17.7 % higher in comparison with the normative values, and 20.0 % higher on the medial hoof. Somewhat bigger differences were revealed on the left hind leg, in particular, 26.6 % on the lateral hoof and 22.2 % – on the medial hoof. It was found that by using the suggested method of animals’ diagnostics, the cows do not need to be fixed, the process of diagnosing is quick, the diagnostics is conducted without contact and as a result of such procedure animals do not experience discomfort and stress. The proposed Hofmir apparatus is a promising method of diagnosing cow hoof pathologies. The proposed equipment (Hofmir apparatus) and the algorithm of its operating enable to reveal a number of pathologies at the beginning of their development, which is quite valuable and important.